Case Report: Exome Sequencing Reveals LRBA Deficiency in a Patient With End-Stage Renal Disease - Taylan, Christina; Wenzel, Andrea; Erger, Florian; Göbel, Heike; Weber, Lutz T.; Beck, Bodo B. (Frontiers in Pediatrics, 2020)
Background: Lipopolysaccharide-responsive and beige-like anchor protein (LRBA) deficiency is characterized by autoimmunity, chronic diarrhea, and immunodeficiency. Minor renal manifestations have been found in a few patients, but kidney disease has not been systematically studied and may remain underdiagnosed in this highly variable entity. Results: Our patient initially presented with pancytopenia, enteropathy, hypogammaglobulinemia, and failure to thrive at the age of 15 months. Chronic kidney disease was diagnosed at 6 years. A renal biopsy taken at 11 years of age showed interstitial nephritis. The patient progressed rapidly to end-stage renal disease (ESRD) and underwent kidney transplantation at the age of 12 years. Bronchiolitis obliterans, post-transplant lymphoproliferative disease (PTLD), and chronic rejection complicated the post-transplant management. Graft loss required reinstitution of hemodialysis within 3 years. After negative results of different targeted sequencing strategies, exome sequencing identified a homozygous nonsense mutation (p.Q1010*) in the LRBA gene more than 21 years after the patient's initial presentation. Conclusions: We report here the development of ESRD and long-term follow-up in a patient with LRBA deficiency. A molecular diagnosis in rare (kidney) disease like LRBA deficiency bears many advantages over a descriptive diagnosis. A precise diagnosis may result in improved (symptomatic) treatment and allows differentiating treatment- and procedure-related complications from manifestations of the primary disease.